2009
DOI: 10.1152/ajpregu.90521.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T-cell function by endogenously produced angiotensin II

Abstract: The adaptive immune response and, in particular, T cells have been shown to be important in the genesis of hypertension. In the present study, we sought to determine how the interplay between ANG II, NADPH oxidase, and reactive oxygen species modulates T cell activation and ultimately causes hypertension. We determined that T cells express angiotensinogen, the angiotensin I-converting enzyme, and renin and produce physiological levels of ANG II. AT1 receptors were primarily expressed intracellularly, and endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
206
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(224 citation statements)
references
References 45 publications
10
206
1
4
Order By: Relevance
“…These results, together with clear experimental evidence that MPO impairs NO availability in an H 2 O 2 -dependent manner, 23 suggest that RAS-mediated leukocyte activation by FFA may facilitate endothelial dysfunction partly through the release of MPO and possibly enhanced leukocyte adhesion. It is reasonably assumed that the release of cytokines and reactive oxygen species from activated T lymphocytes, which has been shown to be Ang dependent, 30 may also adversely modulate vascular function. 31 The extrapolation of our results to patients with visceral fat obesity is not necessarily straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…These results, together with clear experimental evidence that MPO impairs NO availability in an H 2 O 2 -dependent manner, 23 suggest that RAS-mediated leukocyte activation by FFA may facilitate endothelial dysfunction partly through the release of MPO and possibly enhanced leukocyte adhesion. It is reasonably assumed that the release of cytokines and reactive oxygen species from activated T lymphocytes, which has been shown to be Ang dependent, 30 may also adversely modulate vascular function. 31 The extrapolation of our results to patients with visceral fat obesity is not necessarily straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nervous system and RAS share a number of common pro-hypertensive actions (for example, increased vascular resistance and endothelial dysfunction) and both have been implicated in activating the immune system. 60,121,122 Primary hypertension is associated with increased circulating concentration of several inflammatory molecules such as tumour necrosis factor alpha (TNFa), interleukin-6, C-reactive protein and adhesion molecules (for example, P-selectin and intercellular adhesion molecule-1), and vascular inflammation may contribute to the pathophysiology of hypertension. 88,123,124 T-lymphocytes appear particularly critical for Ang II and deoxycorticosterone acetate-salt-induced hypertension and the concomitant vascular and kidney dysfunction.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%
“…88,123,124 T-lymphocytes appear particularly critical for Ang II and deoxycorticosterone acetate-salt-induced hypertension and the concomitant vascular and kidney dysfunction. 121,122,125 T-cell activation is increased by Ang II and leads to the production of pro-inflammatory cytokines. 121 Intriguingly, anti-TNFa therapy (etanercept) has been shown to prevent Ang II-induced hypertension and vascular oxidative stress.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%
“…Recently, a number of studies have demonstrated that RAS activation could play an important role in immunologically induced inflammation (14)(15)(16). In vitro and in vivo studies have shown that Ang II could induce DCs maturation (14,17).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that Ang II could induce DCs maturation (14,17). Additionally, several lines of evidence demonstrate that Ang II induces Th1 and Th17 immune responses and ultimately enhances inflammation in several Ang II-mediated inflammatory diseases (15)(16)(17)(18). However, the direct regulatory effect of losartan on the function of lung DCs and Th cells in ALI remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%